Non-Visitors’ Attitude Towards Kubah National Park’s Roles and Functions - Nor Afiza, Abu Bakar; Dayang Affizzah, Awang Marikan; Salbiah, Edman; Dayang Haszelinna, Abang Ali; Nur Rasyiqah, Adam (Human Resource Management Academic Research Society, 2021)
Besides being a vital component of Malaysia's ecotourism, the biodiversity of national parks is the heart of the existing protected areas and heavily support the domestic, national and international policies on conservation of endangered species, especially in the state of Sarawak which houses a large number of protected species. Therefore, it is imperative to study the behaviour and attitude of ecotourism consumers to ensure sustainable management of national parks. This paper examines the perception of non-visitors regarding the roles, policies and proper operations of national parks in Malaysia, based on data from Kubah National Park (KNP), Sarawak. Findings show that respondents have a very positive attitude towards the roles and functions of KNP. The majority of the respondents’ express eagerness to visit KNP in the future. They agree that KNP is a place to protect the natural beauty of the environment and wildlife. Respondents also acknowledge that KNP protects endangered species and should continue to be protected for the enjoyment of future generation. While wildlife protection and ecotourism activities receive support, respondents regard commercial development, socializing and spiritual fulfilment as inappropriate. The results of this paper are significant in order to maintain management and conservation of KNP.